2007
DOI: 10.5194/adgeo-12-81-2007
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hazards and the press in the western Mediterranean region

Abstract: Abstract. This study analyses press articles published between 1982 and 2005 in an attempt to describe the social perception of natural hazards in Catalonia. The articles included in the database have been classified according to different types of risk. In addition, the study examines the evolution of each type of risk in the press coverage during the study period. Finally, the results have been compared to data provided by insurance companies with respect to compensations paid out for damages. Conclusions sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…The results of the analysis reveal that the press focuses more on the vulnerability to risks (economic and social damage) and less on the actual danger (description and/or explanation of the meteorological phenomenon). It is also necessary to assess in each case all the situational factors involved in the publication of a news item, since the spatial and temporal location of the event need to be taken into account too (Llasat-Botija et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the analysis reveal that the press focuses more on the vulnerability to risks (economic and social damage) and less on the actual danger (description and/or explanation of the meteorological phenomenon). It is also necessary to assess in each case all the situational factors involved in the publication of a news item, since the spatial and temporal location of the event need to be taken into account too (Llasat-Botija et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…some pictures or descriptions). There have been some previous studies that argue the case for use of the press to estimate the social perception of natural risks or climate change (Allan et al, 2000;Delitala, 2005;Lacey and Longman, 1997;Fischer, 1998;Llasat-Botija et al, 2007). The majority approach the use of the press like a proxy-data source to obtain indirect information about frequency and risk magnitude, or a socio-cultural approach.…”
Section: Risk Analysis Through the Mediamentioning
confidence: 99%
“…This increase could be due only to an increase of perception, but not to the actual risk. There are already some previous studies that argue the case for use of the press to estimate the social perception of natural risks or climate change (Delitala, 2005;Lacey and Longman, 1997;Rowe et al, 2000;Fischer, 1998;Llasat-Botija et al, 2007;Tàbara, 2008). On the basis of this relationship, this increase in hail risk perception could be caused by an increase of the press coverage of each event.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this relationship, this increase in hail risk perception could be caused by an increase of the press coverage of each event. In its turn, press coverage could be influenced by external events such as political declarations, elections, the economic situation or other events (Llasat-Botija et al, 2007). But it could also be related to changes in the sensitivity of the population to certain natural hazards, for instance, as a consequence of a strong campaign related to weather modification by cloud seeding.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that floods and droughts are dangerous hazards in the Mediterranean region due both to the number of people affected and the relatively high frequency by which human activities and goods suffer damages and losses (Llasat-Botija et al 2007 [1]). This is especially true for semi-arid regions such as the Middle East.…”
Section: Introductionmentioning
confidence: 99%